Public Private Partnerships and public law in China - Fang, Y (2019)
Public Private Partnerships (PPPs) as one form of government contracts engaging the private sector in infrastructure development have been practised worldwide. Since 2014, PPPs were promoted by the Chinese Central Government with unprecedented strength, and booming PPP practice gives rise to a legal inquiry: how PPP contracts should be conceived in the current system of government contracts in China, which is characterised by a distinction between administrative contracts and private contracts? Contextualising PPPs in the landscape of China’s political economy, investigating policy rationales, regulation and practice of PPPs as well as examining the existing legal debate over the nature of PPP contracts in China, this Thesis argues that PPPs should be classified as administrative contracts to enhance government accountability and better achieve the public interest.